Reduced Microvascular Blood Volume as a Driver of Coronary Microvascular Disease in Patients With Non-obstructive Coronary Artery Disease: Rationale and Design of the MICORDIS Study - Vink, Caitlin E. M.; van de Hoef, Tim P.; Götte, M. J. W.; Eringa, E. C.; Appelman, Yolande (Frontiers in Cardiovascular Medicine, 2021)
Background: Ischemia with non-obstructive coronary arteries (INOCA) is part of the ischemic heart disease spectrum, and is particularly observed in women. INOCA has various mechanisms, such as coronary vasospasm and coronary microvascular dysfunction (CMD). A decreased coronary flow reserve (CFR) and-or increased myocardial resistance (MR) are commonly used to diagnose CMD. However, CFR and MR do not describe all pathophysiological mechanisms underlying CMD. Increased myocardial oxygen consumption (MVO2) normally increases myocardial blood volume (MBV), independently from myocardial blood flow (MBF). In addition insulin enhances MBV in healthy skeletal muscle, and this effect is impaired in INOCA-related conditions such as diabetes and obesity. Therefore, we propose that MBV is reduced in INOCA patients. Aim: To assess whether myocardial blood volume (MBV) is decreased in INOCA patients, at baseline, during hyperinsulinemia and during stress. Design: The MICORDIS-study is a single-center observational cross-sectional cohort study (identifier NTR7515). The primary outcome is MBV, compared between INOCA patients and matched healthy controls. The patient group will undergo coronary function testing using a Doppler guidewire, intracoronary adenosine and acetylcholine to measure CFR and coronary vasospasm. Both the patient- and the control group will undergo myocardial contrast echocardiography (MCE) to determine MBV at baseline, during hyperinsulinemia and during stress. Subsequently, cardiac magnetic resonance (CMR) will be evaluated as a new and noninvasive diagnostic tool for CMD in INOCA patients. Microvascular endothelial function is a determinant of MBV and will be evaluated by non-invasive microvascular function testing using EndoPAT and by measuring NO production in circulating endothelial cells (ECFCs).